2019
DOI: 10.1101/668517
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prepontine non-giant neurons drive flexible escape behavior in zebrafish

Abstract: Many species execute ballistic escape reactions to avoid imminent danger. Despite fast reaction times, responses are often highly regulated, reflecting a trade-off between costly motor actions and perceived threat level. However, how sensory cues are integrated within premotor escape circuits remains poorly understood. Here we show that in zebrafish, less precipitous threats elicit a delayed escape, characterized by flexible trajectories, that are driven by a cluster of 38 prepontine neurons that are completel… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…For example, in zebrafish, the balance of excitation between M-cells is controlled by feedforward inhibition from local neurons and this can contribute to the initial selection of which side is activated during escape (17,29). Modulator circuits in the brain also contribute to mediating a more flexible escape behavior (19,20,(64)(65)(66)(67)(68). Our results now demonstrate an additional layer of processing at the spinal cord level that not only transforms escape commands into motor action, but could provide an additional level of computation that could take into account spinal local inputs to determine the extent of the escape movement and control its trajectory.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in zebrafish, the balance of excitation between M-cells is controlled by feedforward inhibition from local neurons and this can contribute to the initial selection of which side is activated during escape (17,29). Modulator circuits in the brain also contribute to mediating a more flexible escape behavior (19,20,(64)(65)(66)(67)(68). Our results now demonstrate an additional layer of processing at the spinal cord level that not only transforms escape commands into motor action, but could provide an additional level of computation that could take into account spinal local inputs to determine the extent of the escape movement and control its trajectory.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism allowing the modulation of Stage 1 turning angles in the 0 ms and 33 ms treatments could be related to the activity of Mauthner cells and associated neurons, as well as the prepontine neurons (Marquart et al, 2019). Prepontine neurons facilitate the integration of multiple sensory information (visual and auditory) and alter Stage 1 of the escape response (Marquart et al, 2019). It is possible that a similar mechanism may occur in the presence of two visual stimuli; i.e.…”
Section: Discussionmentioning
confidence: 99%
“…a ballistic response) (Sato et al, 2019). In fish, recent work has shown that larval zebrafish may be able to integrate sensory information from multiple threats during delayed escape responses due to a cluster of 38 prepontine neurons that are not part of the fast escape neural pathway (Marquart et al, 2019). This finding suggests that during the initial escape latency (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…No other binary or three component mixture induced statistically significant effects compare to controls. We also analyzed the frequency of long latency C-bends (LLCs), which are normal responses typically elicited by weaker stimuli and that are independent of the Mauthner cell and instead rely on the activation of prepontine neurons (Marquart et al 2019).…”
Section: 3mentioning
confidence: 99%